2012
DOI: 10.1258/ijsa.2012.200312
|View full text |Cite
|
Sign up to set email alerts
|

UK national guideline on safer sex advice

Abstract: Summary: This guideline provides evidence-based guidance on the content of safer sex advice and the provision of brief behaviour change interventions deliverable in genitourinary (GU) medicine clinics. Much of the advice is applicable to other healthcare settings including general practice and clinics providing HIV care. Advice on condom use and effectiveness, oral sex and other sexual practices, testing for sexually transmitted infections (STI) and partner reduction is provided. Advice specific to the transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 0 publications
0
31
0
2
Order By: Relevance
“…(410) and longitudinal studies support the contention that the risk is significantly lower than that for vaginal or anal sex and may be zero in some untreated individuals (45). There is no published estimate for an upper confidence limit for transmission risk through oral sex with undetectable HIV viral load but given that sexual behaviours in both HPTN 052 and the PARTNER study would include oral sex in both heterosexual and MSM couples, it seems that a best estimate of transmission risk for oral sex with undetectable viral load is zero.…”
Section: Recommendationsmentioning
confidence: 76%
“…(410) and longitudinal studies support the contention that the risk is significantly lower than that for vaginal or anal sex and may be zero in some untreated individuals (45). There is no published estimate for an upper confidence limit for transmission risk through oral sex with undetectable HIV viral load but given that sexual behaviours in both HPTN 052 and the PARTNER study would include oral sex in both heterosexual and MSM couples, it seems that a best estimate of transmission risk for oral sex with undetectable viral load is zero.…”
Section: Recommendationsmentioning
confidence: 76%
“…The UK Guidelines on Safer Sex Advice recommend evidence-based behaviour-change interventions for those at higher risk of STIs (including young people), focusing on enhancing communication skills and increasing motivation to adopt safer sexual behaviours. 36 Techniques such as motivational interviewing are recommended to increase motivation to adopt safer sexual behaviours, and the guideline recommends that detailed and tailored information on safer sex should form part of all sexual health consultations (in settings such as general practice as well as sexual health clinics). The NICE guidance on one-to-one interventions to reduce STIs and under-18 conceptions recommends that clinicians assess STI risk when the opportunity arises, for example when someone attends for contraception or registers as a new patient.…”
Section: Sexual Health Promotion In Clinic and Community Settingsmentioning
confidence: 99%
“…Of particular note are NHS Healthcare Improvement Scotland's Standards for Human Immunodeficiency Virus (HIV) Services 38 and the UK National Guideline on Safer Sex Advice. 39 Of note, the latter, while providing evidence-based recommendations, has a remit that covers a range of STIs (i.e. it is not solely concerned with HIV infection prevention).…”
Section: Current Service Provisionmentioning
confidence: 99%
“…39 The authors reported that, in an assessment of 24 sentinel GUM clinics, there was a low level of offer and uptake of behaviour change interventions to higher-risk MSM. They note that reasons for this poor compliance may relate to patient factors (e.g.…”
Section: Current Service Provisionmentioning
confidence: 99%
See 1 more Smart Citation